A Bi-Level Control Strategy for PV-BES System Aiming at the Minimum Operation Cost of BES - Hao, Yuchen; Su, Dawei; Lei, Zhen (Frontiers in Energy Research, 2021)
With the increase penetration of the photovoltaic (PV) energy, the power system stability problem becomes an issue, as the output power of PV plants is with the high intermittence and randomness. To maintain the power stability of the PV plants, battery energy storages (BESs) play an important role as their fast and accurate response speed. However, it is challenging that the BES with multiple sub-modules well responds to the PV power fluctuations resulting from the various influence factors, such as defects, faults, and partial shading. Therefore, a bi-level control strategy is proposed in this paper, aiming at minimizing the operation cost of BES in maintaining the power stability. The control strategy consists of the PV power fluctuations identification block and the mitigation block. In specific, the identification block can output the power fluctuation of a PV system by the PV power fluctuation identification technique. The technique is developed based on the characteristics of PV-string current under electrical faults and partial shading conditions. Meanwhile, the mitigation block can manage the multiple battery sub-modules with different regulation characteristics to meet the power fluctuations. At last, the promising results are obtained by MATLAB\Simulink with the coordinated operation of those two blocks, including the precise condition of the PV system and the optimal power output of each battery sub-modules. Therefore, a comprehensive bi-level control strategy is developed to regulate the operation of battery sub-modules for PV-BES systems.